Efgartigimod versus intravenous immunoglobulin in the treatment of patients with impending myasthenic crisis - Jing Ma; Huiqiu Zhang; Junsen Zhao; Menghan Su; Yingna Feng; Xiaoli Yuan; Dan Liu; Xiaomin Pang; Rongjuan Zhao; Juan Wang; Weisong Duan; Xueli Chang; et al. (Scientific Reports, 2024)
Abstract Impending myasthenic crisis (IMC) is an emergent situation requiring aggressive management to prevent patients from developing myasthenic crisis (MC) in patients with myasthenia gravis (MG). Efgartigimod has been proved to be well tolerated and efficacious in MG patients. The present study aimed to compare the efficacy of efgartigimod and intravenous immunoglobulin (IVIg) in rescuing IMC. IMC patients treated with efgartigimod or IVIg were retrospectively enrolled. The primary outcome was determined as the mean change in MG activities of daily living (MG-ADL) score from baseline to week 1 and 4 after treatment, respectively. Safety was assessed based on medical records during the hospitalization to monitor the adverse events. A total of 9 patients treated with efgartigimod and 10 patients treated with IVIg were enrolled. There were no significant differences in the clinical characteristics at baseline between the two groups (P > 0.05). Compared with the IVIg group, the efgartigimod group had a greater reduction in the MG-ADL score at week 1 (P = 0.035) and week 4 (P = 0.005). One patient in the efgartigimod group had an upper respiratory infection. These findings suggest that efgartigimod is a treatment option for IMC in addition to IVIg and plasma exchange.